Media Sosial dalam Proses Pembuktian Tindak Pidana Informasi dan Transaksi Elektronik - Rionov Oktana; Syukri Akub; Maskun Maskun (CV. Social Politic Genius (SIGn), 2022)
This study aims to examine and analyze social media accounts’ status and seizure procedures in the evidentiary process of cybercrime. This study uses normative legal research with a statute and case approach. The collection of legal materials is carried out using a literature study technique. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the status of social media as legal means of proof in the evidentiary process at trial is regulated in Law No. 11 of 2008 and Law no. 8 of 1981. Electronic evidence can be categorized as proof of indication by fulfilling the formal and material requirements regulated in Law No. 11 of 2008. Meanwhile, seizure procedures of social media accounts in the evidentiary process of cybercrime are preceded by searching mobile phone communication to obtain device specifications. Social media accounts, files, documents, and applications used by cybercrime perpetrators will be found in these specifications. Seizure of social media accounts is regulated in Article 43 section (3) of Law No. 19 of 2016, while the procedure is carried out based on Law No. 8 of 1981. Therefore, it is recommended that the government and law enforcement agencies issue implementing regulations regarding seizing social media accounts as legal means of proof in the evidentiary process of electronic information and transaction crimes. In addition, collaboration between the Ministry of Communications and Informatics and social media platforms is needed to handle more accessible and more efficient cases, mainly regarding seizures of social media accounts used by cybercrime perpetrators. On the other hand, it is necessary to expand the meaning of proof of indication as regulated in Law No. 8 of 1981 in order to be able to emphasize social media proof as a legal means of proof.